2008
DOI: 10.4049/jimmunol.180.7.5067
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 Protein Binding to Lipopolysaccharide Facilitates Transfer of Lipopolysaccharide to CD14 and Enhances Lipopolysaccharide-Mediated TNF-α Production in Human Monocytes

Abstract: LPS-binding protein (LBP) is a central mediator that transfers LPS to CD14 to initiate TLR4-mediated proinflammatory response. However, a possibility of another LPS transfer molecule has been suggested because LBP-deficient mice showed almost normal inflammatory response after LPS injection. In this study, we describe the novel finding that high mobility group box 1 protein (HMGB1) recently identified as a mediator of sepsis has a function of LPS transfer for a proinflammatory response. We used ELISA and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
220
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 236 publications
(236 citation statements)
references
References 55 publications
(62 reference statements)
13
220
0
3
Order By: Relevance
“…29 In addition HMGB1 binding to LPS has been reported to facilitate LPS cellular transformation to a CD14+ profile that enhances LPSmediated TNF-α production in human monocytes. 30 The present study fits with these prior data, and also provides new clues about the mechanisms involved, as described below.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…29 In addition HMGB1 binding to LPS has been reported to facilitate LPS cellular transformation to a CD14+ profile that enhances LPSmediated TNF-α production in human monocytes. 30 The present study fits with these prior data, and also provides new clues about the mechanisms involved, as described below.…”
Section: Discussionsupporting
confidence: 66%
“…3,5,28 Our finding that HMGB1 can enhance LPSinduced lung fibroblast proliferation is novel, yet consistent with findings of cooperative effects in other types of cells, including synovial fibroblasts, macrophages, and human monocytes. [29][30][31] For example, Wahamaa et al 32 showed that HMGB1 increased LPS-induced secretion of cytokines, such as tumor necrosis factor-α (TNF-α), interleukin (IL)-6, and IL-8, in synovial fibroblasts. HMGB1 was also shown to enhance the proinflammatory activity of LPS in activated macrophages by promoting the phosphorylation of p38 mitogen-activated protein kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have also demonstrated up-regulation of different chemokines and cytokines at both transcript and protein levels in HBVPs after exposure to HMGB1 albeit at lower levels than those observed with LPS as HMGB1 constitutes a comparatively weak TLR4 activator (40). In fact, it has been proposed that HMGB1 only exhibits full proinflammatory activity when complexed to LPS (42) because a combination of HMGB1 and LPS results in a higher increase in TNF-␣ production in human peripheral blood monocytes than LPS or HMGB1 treatment alone (43). Alternatively, HMGB1 signaling in HBVPs may be more dependent on CD14 expres- sion than LPS signaling as optimal HMGB1-dependent TLR4 activation seems to require this coreceptor at least in murine macrophages (44).…”
Section: Discussionmentioning
confidence: 99%
“…Post-translational modifications of HMG proteins can alter their interactions with DNA and proteins, and consequently, affect their biological activities (1). HMGB1, for example, could be phosphorylated and/or acetylated by pro-inflammatory signals and translocated to the cytoplasm for secretion (12,13) to induce proinflammatory response (14,15). The binding of HMGN pro-teins to nucleosomes can be altered by HMGN modification.…”
Section: High Mobility Group Nucleosomal Binding Domain 2 (Hmgn2)mentioning
confidence: 99%